(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the athletic satisfaction and passion of elite handball Brazilian athletes. Subjects were 88 women handball athletes, participants of Brazilian Woman Handball Championship - Adult category (2016). The instruments were an identification form, Athletic Satisfaction Questionnaire and Passion Scale. Data were analyzed with Kolmogorov Smirnov, U of Mann Whitney and Spearman correlation coefficient (p<0,05). Results showed that elite Brazilian handball athletes higher satisfaction for individual dedication (Md=5,45), team contribution for task (Md=5,03), team contribution for social (Md=4,96) and individual performance (Md=4,88) dimensions, and harmonious passion (Md=5,65) for sport. There were significant differences (p<0,05) between the levels of competition, indicating that athletes who competing at the international level were more satisfied with team performance (Md = 5,00), skill utilization (Md = 5,40), personal treatment (Md = 4,40), team contribution for social (Md = 4,67) and personal dedication (Md = 5,25). Significant differences were found in all dimensions of athletic satisfaction in function of performance in competition (p<0,05), with higher values presented by medalist athletes. Likewise, differences (p<0,01) were found between medalist and non-medalist athletes in the three dimensions of passion. For medalist athletes, a significant and positive correlation (p<0,01) was found between satisfaction and passion dimensions, with emphasis on personal dedication and harmonious passion (r = 0,39), and obsessive passion (r = 0,38). For non-medal athletes, the results showed significant correlations (p<0,01) between obsessive passion with individual performance (r = 0,47) and ethics (r = 0,45). Still, team integration was correlated with harmonious passion (r = 0,39) and obsessive (r = 0,40). Brazilian elite handball women athletes are satisfied with their contributions to the team and the group’s actions to achieve goals, reflecting on their personal performance, showing a harmonious passion for their sports activity, being these results more evident for the medalist athletes.